2008
DOI: 10.1038/sj.gene.6364454
|View full text |Cite
|
Sign up to set email alerts
|

Systematic expression profiling of innate immune genes defines a complex pattern of immunosenescence in peripheral and intestinal leukocytes

Abstract: Immunosenescence is characterized by a quantitative decline of adequate immune responses, which renders the elderly individual particularly susceptible to bacterial, viral and fungal pathogens. Whereas changes of the aging adaptive immune system (for example, reduced immunoglobulin secretion) have been extensively characterized, alterations of the innate immune system are still poorly understood. The aim of the present study was to systematically examine mRNA expression levels of innate immune genes and proinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Possible explanations for the discrepant findings in our study and that of Noren Hooten et al (2010) may be differences in sample sizes (102 vs. four individuals), ages of the participants (maximum age 105 vs. 64.5 years), phenotypes (healthy aging vs. normal aging), and in the examined tissues (whole blood vs. blood mononuclear cells). Despite its heterogeneity of cell types, whole blood has been shown to be a suitable tissue for reliably monitoring expression changes related to human aging and diseases (McLoughlin et al, 2006;Rosenstiel et al, 2008;Keller et al, 2011). Nevertheless, given the changes in peripheral blood with the aging processes (Paganelli et al, 1992;Pawelec et al, 1997), we cannot rule out the possibility that the observed differential miRNA expression in LLI may also partially reflect alterations in their cell type composition.…”
Section: Confirmation Of Previously Described Aging-related Mirna Biomentioning
confidence: 79%
“…Possible explanations for the discrepant findings in our study and that of Noren Hooten et al (2010) may be differences in sample sizes (102 vs. four individuals), ages of the participants (maximum age 105 vs. 64.5 years), phenotypes (healthy aging vs. normal aging), and in the examined tissues (whole blood vs. blood mononuclear cells). Despite its heterogeneity of cell types, whole blood has been shown to be a suitable tissue for reliably monitoring expression changes related to human aging and diseases (McLoughlin et al, 2006;Rosenstiel et al, 2008;Keller et al, 2011). Nevertheless, given the changes in peripheral blood with the aging processes (Paganelli et al, 1992;Pawelec et al, 1997), we cannot rule out the possibility that the observed differential miRNA expression in LLI may also partially reflect alterations in their cell type composition.…”
Section: Confirmation Of Previously Described Aging-related Mirna Biomentioning
confidence: 79%
“…Why this is so is not clear. One possibility is that the aging immune system, which shows both decrements and derangements in function [52, 53], becomes less capable of clearing senescent cells. In addition, the production of senescent cells may increase with age owing to an age-dependent acceleration of tissue damage – for example, increasing oxidative stress due to progressively more damaged and hence less functional mitochondria [54].…”
Section: Detrimental Effects Of the Saspmentioning
confidence: 99%
“…The adaptive immune system is affected by aging, with a well-documented dysregulation in humoral as well as cell-mediated immune responses (McGlauchlen & Vogel, 2003; Linton & Dorshkind, 2004). Recent studies have begun to document the impact of aging on the innate immune system, but age-related deficits, especially in human subjects, remain incompletely defined (Rosenstiel et al , 2008; Shaw et al , 2010). …”
Section: Introductionmentioning
confidence: 99%